Exploring AI-Assisted Language Learning for EFL Learners’ Speaking Development in Suburban Contexts - Bagus Waluyo (Patria Educational Journal (PEJ), 2026)
This study examines how artificial intelligence (AI)-based tools can support English as a Foreign Language (EFL) learners in suburban universities who face limited opportunities for speaking practice and authentic communication. Using a qualitative phenomenological approach, the research involved 15 students from Universitas Nahdlatul Ulama Blitar and Universitas Merdeka Pasuruan. Data were collected through semi-structured interviews and analyzed using phenomenological reduction, detailed description, and identification of essential meanings. The findings indicate that AI-powered speaking tools enable students to practice independently, receive immediate and non-judgmental feedback, and improve confidence despite restricted human interaction. Participants reported greater flexibility and accessibility in developing speaking skills. However, the study also emphasizes that the effectiveness of AI tools depends on appropriate pedagogical integration, including teacher guidance, alignment with learning objectives, and opportunities for peer collaboration. The study concludes that AI can effectively enhance speaking competence when combined with meaningful human support and instructional facilitation.